Molecular characterization of mandarin (Citrus reticulata Blanco) using ISSR markers - Suárez-Contreras, Liliana Yanet; Arango-Toloza, Michell Juliett; Sánchez-Pabón, Izquel (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2020)
In order to establish the molecular diversity of citrus production systems from Villa Sucre (Colombia), mainly "Creole mandarin", the study analyzed C. reticulata farm’s samples using six ISSR molecular markers. A total of 61 polymorphisms were characterized, 42% of them were highly common, with a mid- average polymorphic information content (PIC) of 0.42 indicating a high polymorphic variation. Molecular relations based in Dice coefficient and the UPGMA algorithm, showed the existing genetic relationships between the crop areas, grouping them in five separate clades and two main subgroups (MDS). This is the first molecular classification done in the area, sets the basis for mandarin crop molecular diversity, and provides vital information for mandarin crop management programs.